2020
DOI: 10.1155/2020/8878911
|View full text |Cite
|
Sign up to set email alerts
|

A Simultaneous Safety Analysis of Crash Frequency and Severity for Highway-Rail Grade Crossings: The Competing Risks Method

Abstract: This paper proposes a mathematical model, the competing risks method, to investigate highway-rail grade crossing (HRGC) crash frequency and crash severity simultaneously over a 30-year period. The proposed competing risks model is a special type of survival analysis to accommodate the competing nature of multiple outcomes from the same event of interest; in this case, the competing multiple outcomes are crash severities, while event of interest is crash occurrence. Knowledge-gain-based benefits to be discovere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 71 publications
(93 reference statements)
0
3
0
Order By: Relevance
“…Ćirović and Pamučar (2013) conclude that: "The most common choice, which of the level crossings should be with active protection (bell and signalflashers), is based on media assessment and pressure from society, as well as possible consequences of increasing accidents and incidents on the level crossings". In the last few years, research has been done on determining the model for assessing the risk of accidents at level crossings (Pasha et al 2020;Keramati et al 2020). A known technique of mathematical programming for measuring the efficiency of complex entities with diverse inputs/outputs, Data Envelopment Analysis -DEA, which makes it possible to determine whether the unit to be decided upon (Decision Making Unit -DMU) is effective or not, used in analyzing the efficiency of 12 operational units representing the nearest cities in which accidents at level crossings in the Republic of Serbia in the period from 2005 to 2014, to reduce the number of accidents (Grujić et al 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ćirović and Pamučar (2013) conclude that: "The most common choice, which of the level crossings should be with active protection (bell and signalflashers), is based on media assessment and pressure from society, as well as possible consequences of increasing accidents and incidents on the level crossings". In the last few years, research has been done on determining the model for assessing the risk of accidents at level crossings (Pasha et al 2020;Keramati et al 2020). A known technique of mathematical programming for measuring the efficiency of complex entities with diverse inputs/outputs, Data Envelopment Analysis -DEA, which makes it possible to determine whether the unit to be decided upon (Decision Making Unit -DMU) is effective or not, used in analyzing the efficiency of 12 operational units representing the nearest cities in which accidents at level crossings in the Republic of Serbia in the period from 2005 to 2014, to reduce the number of accidents (Grujić et al 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results showed that female drivers, younger drivers, drivers from the households with higher income and more frequent use of HRGCs were some of the factors directly associated with inattentive driving at HRGCs. Keramati et al [15] proposed a competing risk method to evaluate the accident frequency and severity at HRGCs for a period of 30 years in North Dakota (U.S.). The study demonstrated that the train detection system, train services, type of roadway surface, railroad and highway traffic, truck percentage and number of highway lanes could influence the accident occurrence likelihood at HRGCs.…”
Section: Risk Contributing Factors At Hrgcsmentioning
confidence: 99%
“…The Florida priority index formula estimates the potential danger of a given level crossing based on the average daily traffic of road vehicles and trains [ 47 ]. The competitive risk model [ 48 ] is a special type of survival analysis designed to correctly assess the marginal probability of an incidence outcome when multiple causes of failure are possible. This method is intensively used in medical research to study the death of patients that can be attributed to competitive events such as cardiovascular and non-cardiovascular causes.…”
Section: Models For Predicting Accidents and Incidents At Level Crossings—a Review Of The Literaturementioning
confidence: 99%